Cytokine and Nitric Oxide-Dependent Gene Regulation in Islet Endocrine and Nonendocrine Cells. Issue 1 (1st December 2021) - Stancill, Jennifer S; Kasmani, Moujtaba Y; Khatun, Achia; Cui, Weiguo; Corbett, John A
Abstract: While exposure to inflammatory cytokines is thought to contribute to pancreatic β-cell damage during diabetes, primarily because cytokine-induced nitric oxide impairs β-cell function and causes cell death with prolonged exposure, we hypothesize that there is a physiological role for cytokine signaling that protects β-cells from a number of environmental stresses. This hypothesis is derived from the knowledge that β-cells are essential for survival even though they have a limited capacity to replicate, yet they are exposed to high cytokine levels during infection as most of the pancreatic blood flow is directed to islets. Here, mouse islets were subjected to single-cell RNA sequencing following 18-h cytokine exposure. Treatment with IL-1β and IFN-γ stimulates expression of inducible nitric oxide synthase (iNOS) mRNA and antiviral and immune-associated genes as well as repression of islet identity factors in a subset of β- and non-β-endocrine cells in a nitric oxide-independent manner. Nitric oxide-dependent expression of genes encoding heat shock proteins was observed in both β- and non-β-endocrine cells. Interestingly, cells with high expression of heat shock proteins failed to increase antiviral and immune-associated gene expression, suggesting that nitric oxide may be an internal "off switch" to prevent the negative effects of prolonged cytokine signaling in islet endocrine cells. We found no evidence for pro-apoptotic gene expression following 18-h cytokine exposure. Our findings suggest that the primary functions of cytokines and nitric oxide are to protect islet endocrine cells from damage, and only when regulation of cytokine signaling is lost does irreversible damage occur. Graphical Abstract: